Evaluation of sexual, tissue and morphological development genes of Nellore cattle submitted to fetal programming - Polizel, Guilherme Henrique Gebim (2021)
The Brazilian beef cattle production occurs largely in the Cerrado and with Nellore animals, with Brachiaria pastures being very common and, in this scenario, the malnutrition of pregnant bovine dams is present in the country due to the greater demand nutrients at this physiological stage. As a result, progeny can be affected in their productivity and lifelong performance. This insult or prenatal nutritional stimulus is called fetal programming. Thus, this thesis aimed to evaluate genes and phenotypes related to sexual precocity, body development and tissue differentiation of young bulls submitted to fetal programming during the rearing phase. For this, during pregnancy, 126 Nellore cows were divided into three nutritional plans (FP, PP and NP, respectively): ⅓ of the dams received protein-energy supplementation for the entire pregnancy, another ⅓ of the cows only in the final third and ⅓ did not receive this nutritional stimulus. During the entire rearing phase, phenotypic data (weight, ultrasound measurements of the carcass and scrotal perimeter) and biological material (Longissimus muscle and semen) were collected to assess the effect of different prenatal supplementation strategies on the 64 analyzed bulls. In the first chapter, an assessment of sexual precocity, morphological and physical characteristics of the semen was carried out and a nutrigenetic study was carried out to assess the animals\' response to prenatal nutritional stimulus. In this chapter it was possible to observe the effects of the frugal phenotype on reproductive characteristics and that the fetal programming has no effect on sexual precocity in Nellore bulls. Furthermore, genotype-environment interaction and some genes associated with SNPs (single nucleotide polymorphism) that explained more than 1% of the genetic variance of the animals between the different treatments were found. In chapter 2, the influence of fetal programming on the phenotypes (rump and backfat thickness, weight, average daily gain, ribeye area, muscle cell area and number of muscle cells in ribeye area) was evaluated during the rearing phase. In this chapter it was possible to observe that the fetal programming influenced the weight of the bulls during the rearing phase, however at the evaluated ages it did not show any effect on the fat thickness nor histological assessments. In addition, prenatal protein-energy supplementation throughout pregnancy showed a tendency towards better average daily gain and ribeye area in bulls throughout the rearing phase. In the third chapter, the transcriptome of 15 bulls was analyzed for differential gene expression in order to assess whether fetal programming had an influence on the animals\' muscle gene expression; and eQTL (expression quantitative trait loci) to assess which genes and metabolic processes were related to the genetic background of the animals evaluated. In this chapter, no differences were found in the differential gene expression between treatments, however the eQTLs found control characteristics related to fetal programming, which may be masking the possible effects of prenatal nutrition. In short, this thesis brings great contributions to the field of fetal programming, with pioneering studies, contributing to the discovery of mechanisms associated with maternal nutrition and the impacts on their offspring.